Keefektifan Biblioterapi untuk Meningkatkan Resiliensi Siswa Yatim Piatu Penghuni Panti Asuhan - Munawaroh, Eem; Sofyan, Afriyadi (Jurnal Kajian Bimbingan dan Konseling, 2018)
This study aimed to examine the effectiveness of bibliotherapy to improve three factors of resilience, namely: aspects of I Have; I Am; and I Can, for orphaned students who live in orphanages. The research subjects were 21 orphaned students selected using purposive sampling technique. The quantitative research used the latin square method and statistical analysis paired t-test to analyze the data. The analysis technique of the instrument validity use Spearman. Meanwhile, the analysis technique of instrument reliability used Alpha Cronbach. The results showed that bibliotherapy can significantly improve the three factors of resilience.